Linguistic image of an opposition journalist in the pragmatic perspective: Речевой имидж оппозиционного журналиста в прагмалингвистическом ракурсе - Sładkiewicz, Żanna (Przegląd Wschodnioeuropejski, 2020)
The paper presents the linguistic image of an opposition journalist in the pragmatic perspective, i.e. taking into account the dominant image-making communicative strategies. The author defines the concept of a personal image and presents a model for describing a linguistic image. The strategic and tactical organization of the linguistic image of an opposition journalist is analyzed on two levels: communicative and textual (content). The communicative component is realized through a wide range of self-representative, phatic and fasciation strategies aimed at attracting the target recipient and involving him emotionally in the implementation of the discursive principle of dialogism. The content component is implemented through the strategy of discrediting and tactics of nomination, intensification, reductionism, fragmentation, as well as modeling the socio-political reality in the temporal aspect. As a result, the image of a categorical critic, an expert, an intellectual and truth-teller is created.